2020
DOI: 10.1093/ajcn/nqz259
|View full text |Cite
|
Sign up to set email alerts
|

Association between sustainable dietary patterns and body weight, overweight, and obesity risk in the NutriNet-Santé prospective cohort

Abstract: Background Improving the sustainability of current food systems may prevent future public health, environmental, and social concerns. Objective Our objective was to investigate the associations between sustainable dietary patterns, assessed using the Sustainable Diet Index (SDI), and the risk of obesity, overweight, and weight gain in French adults, with a prospective design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 45 publications
3
46
2
1
Order By: Relevance
“…On the other hand, our results suggest that students with excessive BF, in addition to showing lower dietary quality, also have higher GHGE associated with their diets. These results are consistent with those of Seconda et al (99) who observed that a sustainable diet, from environmental, nutritional, economic and sociocultural perspectives, exerts a potential protective role against weight gain, being overweight and obesity. Moreover, Vieux et al (55) found that when energy intake was reduced to meet individual energetic needs, diet-associated GHGE was reduced by up to 10 %.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, our results suggest that students with excessive BF, in addition to showing lower dietary quality, also have higher GHGE associated with their diets. These results are consistent with those of Seconda et al (99) who observed that a sustainable diet, from environmental, nutritional, economic and sociocultural perspectives, exerts a potential protective role against weight gain, being overweight and obesity. Moreover, Vieux et al (55) found that when energy intake was reduced to meet individual energetic needs, diet-associated GHGE was reduced by up to 10 %.…”
Section: Discussionsupporting
confidence: 93%
“…In any case, the method used for determining GHGE is a feasible alternative that has been applied in previous studies quantifying GHGE (54,55,116) . Third, the university students' diets were assessed by focusing on two sustainability dimensions, and further investigation should consider the use of indices such as Sustainable Diet Index which include other dimensions of sustainability such as economic and sociocultural aspects (99) . Moreover, only one of the relevant environmental indicators associated with food consumption was used; it would be convenient to consider multiple measures of sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The SDI is an index that features four sub-indices (nutritional, environmental, economic, and food practices), which are scored from 1 to 5 points, resulting in an overall SDI score of 4 to 20 points. As a result, the authors observed that lower SDI scores were associated with a higher risk of obesity and being overweight, when compared to individuals with higher SDI scores [27].…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the aforementioned studies, which evaluated the relationship between obesity indicators and EAT-Lancet-based indices, there was a population-based study, carried out by Seconda et al [27], which assessed the relationship between the Sustainable Diet Index (SDI) and excess weight and obesity in French adults participating in the NutriNet-Santé study. The SDI is an index that features four sub-indices (nutritional, environmental, economic, and food practices), which are scored from 1 to 5 points, resulting in an overall SDI score of 4 to 20 points.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, DP very recently started to take effects beyond health outcomes into account and implications in relation to sustainability and environmental impact have come into focus. Yet, only very few studies have addressed sustainability aspects in exploring DP to-date [14,15,[125][126][127][128]. Thus, there is a strong need to investigate the broader impact of diets on the environment and link these to disease prevention, for which DP analysis has the means to respectively expand its scope and close the gap of analyses of sustainable DPs with chronic disease risk.…”
Section: Summary and Implications For Future Researchmentioning
confidence: 99%